Radiative characteristics of laminar Eucalyptus Globulus flames at different coflows - Pinto, P.; Severino, G.; Cruz Villanueva, J.J.; Rivera, J.; Demarco, R.; Reszka, P.; Fuentes, A. (Elsevier, 2024)
Studying the interplay between heat transfer mechanisms in a burning wildland fuel layer enables to better understand wildfire behavior. This works aims to assess the effect of air flowing through wildland fuels on the radiative properties of a small-scale flame produced with such fuels. Well-controlled flames are produced with Eucalyptus globulus leaves of reduced size imposing three increasing air flows in a small-scale configuration. Mass loss measurements are experimentally obtained and modeled to determine the mass loss rate of the fuel sample. The view factor between the flame and a radiometer is estimated with a contour technique, while color pyrometry is employed to retrieve soot temperature. View factor decreases with time at a larger rate than flame height. Radiation emitted by the flame decreases with time, while radiant fraction first reaches a peak and further decreases until extinction. View factor, thermal radiation and radiant fraction first decrease with air flow, then these variations are slight. The relation between normalized radiant fraction and flame height is independent of air flow. Soot temperature first increases with air flow, then remains almost unchanged. Therefore, smaller air flows through wildland fuels affect the radiant properties of a flame produced with these fuels, but larger flows might not exert this influence.
Keywords: Thermal radiation; Flame radiative properties; https://purl.org/pe-repo/ocde/ford#2.01.05